Ethylene Production by Pseudomonas syringae Pathovars In Vitro and In Planta - Weingart, H. (1997)
Significant amounts of ethylene were produced by Pseudomonas syringae pv. glycinea, pv. phaseolicola (which had been isolated from viny weed Pueraria lobata [Willd.] Ohwi [common name, kudzu]), and pv. pisi in synthetic medium. On the other hand, the bean strains of P. syringae pv. phaseolicola and strains of 17 other pathovars did not produce ethylene. P. syringae pv. glycinea and P. syringae pv. phaseolicola produced nearly identical levels of ethylene (about 5 x 10(sup-7) nl h(sup-1) cell(sup-1)), which were about 10 times higher than the ethylene level of P. syringae pv. pisi. Two 22-bp oligonucleotide primers derived from the ethylene-forming enzyme (efe) gene of P. syringae pv. phaseolicola PK2 were investigated for their ability to detect ethylene-producing P. syringae strains by PCR analysis. PCR amplification with this primer set resulted in a specific 0.99-kb fragment in all ethylene-producing strains with the exception of the P. syringae pv. pisi strains. Therefore, P. syringae pv. pisi may use a different biosynthetic pathway for ethylene production or the sequence of the efe gene is less conserved in this bacterium. P. syringae pv. phaseolicola isolated from kudzu and P. syringae pv. glycinea also produced ethylene in planta. It could be shown that the enhanced ethylene production in diseased tissue was due to the production of ethylene by the inoculated bacteria. Ethylene production in vitro and in planta was strictly growth associated.